Film Studies and Translation Studies: Two Disciplines at Stake in Audiovisual Translation - Chaume, Frederic (Meta, 2004)
AbstractAudiovisual texts are usually built according to the conventions of film language, a complex language that overcomes linguistic communication and has its own rules and conventions. In film language it is possible to distinguish several signifying codes which complement and frame words and linguistic meaning. This paper will focus on the interplay of non-linguistic codes in film language and audiovisual translation. In the first place, I will argue that for the analysis of audiovisual texts from a translational perspective at least the theoretical contributions of Translation Studies and those of Film Studies are necessary. Then, I will review the different models of analysis of audiovisual texts offered from the perspective of Translation Studies. Finally, I will introduce a new paradigm based on Film Studies, and present the signifying codes that primarily affect translation operations in the transfer. I will also illustrate these codes with a number of non-linguistic signs and their representation in the text, and will finally discuss the influence of such signs on translation operations.